STRATEGI BAURAN PEMASARAN UNTUK INDUSTRI JAMU SKALA KECIL DENGAN MENGGUNAKAN SISTEM PAKAR - KUSNANDAR KUSNANDAR (Sepa, 2021)
Indonesia has many kind of herb-medicinal plant, therefore development of small-scale herb-medicinal industry is a strategic effort. The aim of this research was to design an expert system for marketing mix strategy.